Opportunity Youth: Insights and Opportunities for a Public Health Approach to Reengage Disconnected Teenagers and Young Adults. (November 2018) - Mendelson, Tamar; Mmari, Kristin; Blum, Robert W.; Catalano, Richard F.; Brindis, Claire D.
Approximately 1 in 9 teenagers and young adults aged 16-24 in the United States is currently disconnected from school and employment. These disconnected young people (ie, opportunity youth) are not only at high risk for long-term emotional, behavioral, and health problems, but they also represent a loss of human capital, with high social and economic costs. In this article, we offer a public health perspective on opportunity youth by describing their distribution in the population and consequences of their disconnection; proposing a conceptual model of the issue based on epidemiological principles, life course development concepts, and ecological theory; and recommending multisector strategies for preventing disconnection of young people and reengaging opportunity youth. A public health approach to the problem of opportunity youth would involve developing and investing in youth monitoring data systems that can be coordinated across multiple sectors, consolidating both the delivery and funding of services for opportunity youth, developing policies and programs that encourage engagement of young people, and fostering systematic approaches to the testing and scaling up of preventive and reengagement interventions.